Graves‘ disease in children and adolescents in Iceland - Þórsson, Þórbergur Atli; Bjarnason, Ragnar; Jónasdóttir, Soffía Guðrún; Jónsdóttir, Berglind (Laeknabladid, 2022)
INTRODUCTION: Graves‘ disease is an autoimmune disease in which autoantibodies cause an increase in the production of thyroid hormones, and is the most common cause of thyrotoxicosis in children. Symptoms in children are often more obscure than in adults. The aim of the study is to assess the incidence of Graves’ disease in children and adolescents in Iceland over the span of two decades (2001-2021), and furthermore to investigate if the incidence rate has increased, as well as to describe treatment options and disease recurrence. MATERIAL/METHODS: This retrospective descriptive study included all children diagnosed with Graves‘ disease in the years 2001-2021 in Iceland. Information was obtained from the Directorate of Health‘s drug database and from ICD-10 diagnoses at Landspítali – The National University Hospital. RESULTS: In total, 57 children and adolescents were diagnosed with Graves’, the overall incidence rate was 3.5/100,000 person-years. Gender ratio was 1:2.7 (male : female) and the mean age at diagnosis was 13.6 for boys and 13.9 years for girls. Of those 12 individuals currently receiving drug therapy (21.8%), four patients have had disease relapse. Thirteen patients reached an euthyroid state with medication (23.7%), 25 received treatment with radioactive iodine (45.5%) and 5 underwent surgery (9.1%). Boys were more likely to relapse. Disease recurrence was 31.8%. CONCLUSION: The incidence of Graves‘ disease did not increase during the study period. The disease was more common in girls, although the gender ratio was lower than expected. Antithyroid drugs were the first choice in treatment and radioactive iodine was the most common permanent treatment option. Disease recurrence was common. A possible relationship between the duration of the original drug therapy and disease recurrence should be investigated.